Impact of tiered restrictions in December 2020 on COVID-19 hospitalisations in England: a synthetic control study - Daniel Hungerford; Benjamin Barr; Mark Green; Marta García-Fiñana; Iain Buchan; Xingna Zhang (BMJ Open)
Objectives To evaluate the effectiveness of localised Tier 3 restrictions, implemented in England in December 2020, on reducing COVID-19 hospitalisations compared with less stringent Tier 2 measures and the variations by neighbourhood deprivation and the prevalence of Alpha (B.1.1.7) variant, the primary variant of concern then, to measure hospital services’ burden and inequalities across different communities.Design Observational study using a synthetic control method, comparing weekly hospitalisation rates in Tier 3 areas to a synthetic control from Tier 2 areas.Setting England between 4 October 2020 and 21 February 2021.Participants 23 million people under Tier 3 restrictions, compared with a synthetic control group derived from 29 million people under Tier 2 restrictions.Interventions Tier 3 restrictions in designated areas were implemented from 7 December 2020, imposing stricter limits on gatherings and hospitality than Tier 2, followed by a national lockdown on 6 January 2021.Primary and secondary outcome measures Weekly COVID-19-related hospitalisations for neighbourhoods in England over 11 weeks following the interventions.Results Implementing Tier 3 restrictions were associated with a 17% average reduction in hospitalisations compared with Tier 2 areas (95% CI 13% to 21%; 8158 (6286 to 9981) in total). The effects were similar across different levels of neighbourhood deprivation and prevalence of the Alpha variant.Conclusions Regionally targeted Tier 3 restrictions in England had a moderate but significant effect on reducing hospitalisations. The impact did not exacerbate socioeconomic inequalities during the pandemic. Our findings suggest that regionally targeted restrictions can be effective in managing infectious diseases.